Humor styles and perceptions of college students in Central Luzon - Torres, Joel M. (Animo Repository, 2020)
Gender is viewed as a system of meaning that affects access to power, status, and material resources, while humor, as a discourse mode, is considered a strategy for social interaction. It is within this theoretical underpinning that women and men use humor in same-gender and mixed-gender settings as a means of gender construction. Though humor style between male and female has been extensively investigated in the foreign context, it has been remained unexplored in the Philippine setting. Likewise, even in the Western context there is a scanty research that looked into perceived offensiveness of the different humor types. It is also interesting to find out how other genders, beyond the male and female dichotomy such as the members of the gay and lesbian community perceived the offensiveness of the different humor types and to determine their humor style as well. Hence, this quantitative study offers initial findings as regards gender divide in humor styles and perception among 120 university students in Central Luzon. © 2020 Asian EFL Journal Press. All rights reserved.